RESEARCH ON THE EFFICIENCY OF FLEXIBLE PROTECTION OF OBJECTS FROM MECHANICAL DAMAGE - Kostenko, O.; Shpylka, M.; Lapenko, T.; Dudnyk, V.; Drozhchana, O.; Klymenko, A.; Shpylka, A. (Scientific Progress & Innovations, 2022)
In modern conditions of intensive development of technological transport, means of protection against mechanical damage are important to ensure safe conditions for people, equipment and building elements. The paper substantiates the need to use protection in the form of fences to save the lives and health of personnel, industrial equipment and building structures. Traditionally, such fences were made mainly of steel or concrete. However, flexible protection made of polymeric materials has recently become widespread. The peculiarity of such fences is that they are almost entirely made of elastic polymeric materials. This allows you to stretch the distribution of energy absorption over time and thus significantly reduce the impact force compared to "traditional" steel and concrete protections under equal conditions. In contrast to traditional metal protection, the reduction of impact force in the case of flexible protection allows you to: avoid tearing anchors out of the concrete floor; avoid damage to the impact object (cargo, vehicles, etc.); maintain a presentable type of protection during operation; significantly reduce the force of inertia that affects drivers when being injured. The purpose of this work is to determine the effectiveness of such protection. To achieve this goal, the analysis of the data from literature sources are analysed, the types of protection and its functional purpose are considered and experimental studies are conducted. The research was done at Politon-Ukraine LLC, which is the only manufacturer of flexible protection in Ukraine. The experiment was performed by the method of crash test on the impact stand with the subsequent application of the visual method of damage assessment and direct measurement of absolute linear values of deformations of structures. Tables have been created and graphs of the dependence of the mass and velocity of the object hitting the fence under the maximum impact force allowed for the structures under investigation have been constructed. The research has fully confirmed the effectiveness of the use of flexible protection of work areas and production facilities. They have good strength values and high flexibility (in collisions the protection is not damaged but only absorbs the impact, there is no residual deformation under the standard force of impact).